Defect Profiling of Oxide‐Semiconductor Interfaces Using Low‐Energy Muons - Maria Mendes Martins; Piyush Kumar; Judith Woerle; Xiaojie Ni; Ulrike Grossner; Thomas Prokscha (Advanced Materials Interfaces, 2023)
Abstract Muon spin rotation with low‐energy muons (LE‐µSR) is a powerful nuclear method where electrical and magnetic properties of surface‐near regions and thin films can be studied on a length scale of ≈200 nm. This study shows the potential of utilizing low‐energy muons for a depth‐resolved characterization of oxide‐semiconductor interfaces, i.e., for silicon (Si) and silicon carbide (4H‐SiC). The performance of semiconductor devices relies heavily on the quality of the oxide‐semiconductor interface; thus, investigation of defects present in this region is crucial to improve the technology. Silicon dioxide (SiO2) deposited by plasma‐enhanced chemical vapor deposition (PECVD) and grown by thermal oxidation of the SiO2‐semiconductor interface are compared with respect to interface and defect formation. The nanometer depth resolution of LE‐µSR allows for a clear distinction between the oxide and semiconductor layers, while also quantifying the extension of structural changes caused by the oxidation of both Si and SiC. The results demonstrate that LE‐µSR can reveal unprecedented details on the structural and electronic properties of the thermally oxidized SiO2‐semiconductor interface.